“EVERYBODY CAN BE A HERO”: KAJIAN REPRESENTASI PAHLAWAN DALAM IKLAN TELEVISI M-150: “EVERYBODY CAN BE A HERO”: KAJIAN REPRESENTASI PAHLAWAN DALAM IKLAN TELEVISI M-150 - Permana, Rangga; Suzan, Nessa (PT. RANESS MEDIA RANCAGE, 2023)
Commercials on television play a role in displaying the symbols that make up the meaning of